Selektion und Bias in traditionellen und Internet-Informationsintermediären: Forschungsstand - Katharina Leyrer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2018)
– The selection of information on the internet is causing massive concerns and discussion. Critics fear the polarization of internet users and warn of echo chambers and filter bubbles. Especially search engines and social networking sites are being held responsible: as information intermediaries they are positioned between content producers and recipients, selecting and rating content. However, empirical findings on selection and bias in internet information intermediaries are scarce and disparate. Moreover, the preselection of information by intermediaries is not a specific characteristic of the digital world, but is equally done by traditional intermediaries such as mass media, bookshops or libraries. This paper summarizes the current state of research on selection and bias in traditional and internet information intermediaries. Different concepts, definitions and implications of the term information intermediary are analyzed in the context of the adjacent term gatekeeper. Furthermore, empirical findings on the theories of filter bubbles, echo chambers and fragmentation are summed up, as well as the state of knowledge on selection in different types of intermediaries. As a basis for further research, two models for analyzing selection and bias in intermediaries are introduced: Bozdag's Filter Model and Jürgens & Stark's Intermediary Effects Model. Lastly, aspects that distinguish selection in internet information intermediaries from selection in traditional contexts are compiled. This paper concludes that the production or reinforcement of bias and fragmentation by internet intermediaries is not sufficiently proven. Moreover, there is a research gap on whether traditional intermediaries have comparable effects. Further research requires a comprehensive analysis on the selection mechanisms in both traditional and internet information intermediaries.
urn:nbn:de:bvb:29-opus4-102405
Keywords: 000; Bias; Bibliothek; Buchhandlung; Echokammer; Filterblase; Fragmentierung; Gatekeeper; Informationsintermediär; Journalismus; Literaturkritik; Multimedia-Plattform; Selektion; Soziale Netzwerk-Seite; Suchmaschine